1984
DOI: 10.1111/j.2044-8295.1984.tb01895.x
|View full text |Cite
|
Sign up to set email alerts
|

An investigation into component and configural processes underlying face perception

Abstract: The nature of the processes underlying face perception was examined in two different paradigms using the same set of stimuli varying on three dimensions of two values each. In a simultaneous matching task, both latencies and errors were found to decrease as the number of differences between stimuli increased. Regression analyses showed that the manipulated features interactively contributed to these variations when the faces were presented in their normal upright orientation, whereas no evidence of an interact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
406
1

Year Published

1990
1990
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 465 publications
(422 citation statements)
references
References 20 publications
15
406
1
Order By: Relevance
“…The hypothesis of Bradshaw and Wallace (1971), that face perception involves parallel perception of features, captures the idea that all parts of the face are perceived simultaneously. However, this is a weaker notion of overall structure or gestalt than the hypothesis of Sergent (1984), in which the parts are not only perceived together but influence one another so that, in effect, the "whole is more than the sum of its parts." Rhodes's (1988) concept of configurational information captures yet another way in which face perception might transcend local feature perception, by involving nonlocal features consisting of relations among local features.…”
Section: Hypotheses About Face Representationmentioning
confidence: 93%
See 2 more Smart Citations
“…The hypothesis of Bradshaw and Wallace (1971), that face perception involves parallel perception of features, captures the idea that all parts of the face are perceived simultaneously. However, this is a weaker notion of overall structure or gestalt than the hypothesis of Sergent (1984), in which the parts are not only perceived together but influence one another so that, in effect, the "whole is more than the sum of its parts." Rhodes's (1988) concept of configurational information captures yet another way in which face perception might transcend local feature perception, by involving nonlocal features consisting of relations among local features.…”
Section: Hypotheses About Face Representationmentioning
confidence: 93%
“…In addition, because Rhodes did not conduct similar analyses with patterns other than faces, she did not draw any conclusions about how face perception differs from the perception of other patterns. Yet another formulation of the idea that overall structure or gestalt is important in face perception comes from Sergent (1984), who applied Garner's (1974) framework of dependence versus independence of stimulus feature processing to faces and suggested that the perception of facial features shows dependency or mutual influence. She analyzed participants' performance in a speeded matching task and a similarity rating task and found that the effects of combinations of features could not always be predicted by the effects of the features individually.…”
Section: Hypotheses About Face Representationmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that there was strong masking with the masks containing faces, there was medium-level masking with inverted faces, disorganized faces and faces without internal elements, and there was no masking with masks containing objects or noise. These results can be explained by the fact that masks hide configurational information about the face, which seems to be essential to recognize complex stimuli (Collishaw & Hole, 2000;Haig, 1984;Hole, 1994;Sergent, 1984;Tanaka & Farah, 1993;Young, Hellawell & Hay, 1987;Sinha, 2002). Uttal, Baruch & Allen (1997) tried to generalize the effect obtained by Harmon and Julesz (1973) Hence, the results show effects of perceptual organization on the recognition process, which are as important as the energetic distribution of SFs.…”
Section: Empirical Evidence Supporting Configurational Properties: Ismentioning
confidence: 98%
“…How is recognition achieved with these faces? To recognise a face, there are at least two strategies that could be used: one could process the configural relationship between the features, or one could engage in piecemeal processing of information from the features themselves (Sergent 1984). There is evidence that either of these two processing modes can be used independently of the other as a basis for recognition, and that participants in face-recognition experiments may be quite flexible in which strategy they use (eg Hole 1994;Collishaw and Hole 2000).…”
Section: Discussionmentioning
confidence: 99%